2014
DOI: 10.1080/13504851.2014.922663
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between commuting time and workers’ utility

Abstract: Numerous studies have looked at the multitude of aspects affecting the utility workers gain from their job. Within these studies, a common proxy for utility is job satisfaction, measured as a self-reported score. A variable often neglected within this research has been commuting time and modes of transport. This article utilizes a unique survey conducted in a UK city region and analyses the effect of commuting time and mode of transport on self-reported job satisfaction. Two cohorts of respondents are construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Similarly, whether longer commutes associate with lower job satisfaction appears to depend on factors such as whether employees believe they are paid inappropriately (Robles, 2018) or whether employees are engaged in knowledge work (Torrent‐Sellens et al, 2018). These boundary conditions may explain inconsistencies in detecting a commuting–job satisfaction relationship that we observed across the history of this research theme (Clark et al, 2019; Crawley, 2014; Novaco et al, 1990; Sarver, 2017).…”
Section: Between‐person Commuting Spillovermentioning
confidence: 84%
See 2 more Smart Citations
“…Similarly, whether longer commutes associate with lower job satisfaction appears to depend on factors such as whether employees believe they are paid inappropriately (Robles, 2018) or whether employees are engaged in knowledge work (Torrent‐Sellens et al, 2018). These boundary conditions may explain inconsistencies in detecting a commuting–job satisfaction relationship that we observed across the history of this research theme (Clark et al, 2019; Crawley, 2014; Novaco et al, 1990; Sarver, 2017).…”
Section: Between‐person Commuting Spillovermentioning
confidence: 84%
“…However, statistical power considerations may also underlie the lack of clarity in a bivariate commuting–job satisfaction relationship, as sample sizes have typically been much larger in studies in which an association has been detected ( N = 682–26,551; Clark et al, 2019; Crawley, 2014; Koslowsky & Krausz, 1993; Robles, 2018; Torrent‐Sellens et al, 2018) than in studies in which this potential co‐variation has not been supported ( N = 82–284; Novaco et al, 1990; Sarver, 2017). This suggests that the magnitude of the relationship of commuting experiences with job satisfaction may be rather modest and thus difficult to detect at smaller sample sizes.…”
Section: Between‐person Commuting Spillovermentioning
confidence: 99%
See 1 more Smart Citation
“…The British case is also studied by Dickerson, Hole and Munford () who, in contrast to previous studies, found evidence that a longer commute has a negative impact on leisure time satisfaction, but not on life satisfaction. Lastly, in his study for Cardiff, Crawley () finds that commuting time has a negative impact on job satisfaction regardless of the mode of transport used, with the exception of workers with higher incomes. In a novel approach, this paper focuses on the impact of commuting on job and housing satisfaction differentiating between self‐employed individuals and employees, providing thus new evidence on the effects of commuting for self‐employed workers, a group not considered by the previous literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sakanishi () discovered significant disparities in time allocation including commuting time and employment patterns between sexes because of differences in household duties. Crawley () indicated that commuting time adversely influences workers' utility. Swärdh and Algers () presented both spouses in two‐earner households evaluate the value of wife's commuting time higher than that of husband because women undertake greater responsibility for household tasks.…”
Section: A Theoretical Model Of Time Allocation and Commuting Decisionmentioning
confidence: 99%